Deformation in transversely isotropic thermoelastic thin circular plate due to multi-dual-phase-lag heat transfer and time-harmonic sources. Issue 1 (1st January 2020) - Lata, Parveen; Kaur, Iqbal; Singh, Kulvinder
Abstract: In this paper, the distortion in homogeneous transversely isotropic thermoelastic (TIT) axisymmetric 2-D thin circular plate with two temperature due to time-harmonic sources have been analysed. The mathematical model has been formed for the rotating thin circular plate with multi-dual-phase-lag generalized heat transfer and has been converted to dimensionless form. The Hankel transform method has been employed to solve the mathematical model. A bicubic equation obtained for nontrivial solution of mathematical model so obtained is solved using MATLAB software. A normal force of unit magnitude and a cubical thermal source and vanishing tangential stress at the boundaries has been taken as boundary conditions. As an application a constant load and a decaying heat source in the radial and axial direction of the thin circular plate has been taken. The displacement components, conductive temperature, and stress components are computed in the transformed domain and numerical inversion techniques are used to find the expressions in the physical domain. The effects of time harmonic frequency and rotation with two temperatures have been represented graphically using MATLAB and analysed for multi-dual phase lag model of heat transfer. Some particular cases have also been discussed.